Two chemotherapeutic agents expand stem-like CD62L+CD8+ T cells in antitumor immune responses - Ruan, Xiaokang; Wu, Linwei; Tang, Zijian; Li, Yao; Wang, Jin; Jiang, Haolin; Zhang, Li; Wang, Shengjia; Chen, Zhaoqiang; Yuan, Chenlei; Xia, Yujian; Pan, Yan; et al. (Frontiers in Immunology, 2025)
IntroductionRecent findings reveal that the precursors of exhausted CD8+ T (CD8+ Tpex) cells possess stem-like signatures in tumor immunity, which originate from tumor draining lymph node (TdLN)-derived tumor-specific memory (CD8+ TTSM) cells. Both of these T subsets can be collectively referred to as stem-like CD8+ T cells, which demonstrate robust self-renewal ability and can proliferate and differentiate into transitory effector-like exhausted T cells (Texint). There are reports that chemotherapeutic drugs can promote the antitumor immune responses of patients by increasing the number of CD8+ T cells; however, whether chemotherapeutic drugs increase these two stem-like CD8+ T cells remain further exploration.MethodsTpex cell-associated subpopulations in human colorectal tumors were analyzed by using single-cell sequencing data. CT26 and B16 tumor models of wild type and Eomes conditional knockout mice were constructed, and the changes of TTSM, Tpex and Tex subsets in mice were dissected by flow cytometry after treatment with decitabine (DAC), doxorubicin (DOX) and 5-Fluorouracil (5-FU).ResultsIn this study, we demonstrated that DAC and 5-FU expanded CD8+ TTSM cells in TdLNs. At the same time, we validated that DAC and 5-FU substantially promoted the expansion of CD62L+CD8+ Tpex cells and subsequently increased effector function of CX3CR1+ CD8+ Texint cells. In addition, the conditional knockout of transcription factor Eomes in CD8+ T cells partially eliminated DAC-amplified CD62L+ CD8+ Tpex cells, but had no effect on such CD8+ T subset expanded by 5-FU.ConclusionThe present study demonstrated that both DAC and 5-FU promoted the differentiation of stem-like CD8+ TTSM cells in TdLNs and significantly enhanced the differentiation and expansion of stem-like CD62L+ CD8+ Tpex and CX3CR1+ Texint cells in tumor microenvironment. The knockout of Eomes partially influenced the role of DAC in promoting the differentiation and expansion of stem-like CD8+ T cells.